Heavy metals concentrations in some Kurdish rice (Oryza sativa L.) short grains cultivated in Iraqi Kurdistan region and its health risk assessment. - Othman Kareem Qadir (Zanco Journal of Pure and Applied Sciences, 2023)
The aim of the current research was to evaluate the heavy metals contamination in Kurdish rice from the main rice-producing areas in Kurdistan and its health risk assessment. The Kurdish rice samples were collected from different locations and the concentration of heavy metals was measured by using Inductively Coupled Plasma-optical emission spectrometry (ICP-OES). The Estimated Daily Intake (EDI) was also calculated to evaluate the potential health risk assessment for the Kurdish local population through rice consumption. The mean EDI values from the rice consumption of most Kurdish rice samples were significantly higher than the safe limits set by FAO/WHO. The heavy metals were detected in the descending order Fe > Mn > Zn > Cu > Cr > Ni > As > Co > Cd in the rice samples. The results demonstrate that Kurdish rice from the investigated region has been contaminated with some heavy metals (As, Cr, Mn and Ni) which is probably linked to the used wastewater for irrigation, fertilisers and soil contamination. Overall, the local population's health might be at risk due to the combination of various metals. Therefore, strict food safety regulations are recommended for cereal crops, as well as, regular monitoring of soil contamination, water quality, application of fertilisers and pesticides in the agricultural areas in Iraqi Kurdistan.